Diabetes Mellitus Insights and Perspectives - Oguntibeju, Oluwafemi O. (IntechOpen, 2013)
The fundamental treatment and management goals in diabetes mellitus are to control and normalize blood glucose levels and to prevent diabetic complications. It also includes maintaining normal growth and development and normal body weight. Proper diet, regular exercise, weight control and different therapeutic agents are the mainstays of diabetic care and management. Weight reduction and exercise have been shown to improve tissue sensitivity to insulin and allow its proper use by target tissues. It is obvious that medical management and goals of therapy for diabetes mellitus have changed since the publication of the Diabetes Control and Complications Trial in 1993. Recent studies have shown that the risk of developing retinopathy can decrease by 76% in properly managed diabetic patients when compared to control group and that clinical and laboratory signs and symptoms of nephropathy and neuropathy can also decrease by 54 to 60%. Modern approaches to the management of diabetes mellitus embrace holistic options and this book addressed various approaches in the management of diabetes mellitus.